Brand metrics that matter - Muntinga, Daan, ....-; Eelen, Jiska, ....-; Bernritter, Stefan, ....- (Amsterdam : SWOCC, 2017)
For more and more organizations, brands are crucially important business assets. Measung how their brands are perceived in the marketplace is therefore essential. Selecting the right brand metrics, however, is a challenge. A sheer unmanageable number of metrics demand marketer's considertin. But which ones are really important? This publication serves as a guide to selecting the brand metrics that matter. It contends that measuring is a highly tailor-made activity: which metrics matter varies from brand to brand and time to time. Moreover, it proposes that brand measurement should focus on gaining foresight rather than insight. Offering a step-by-step brand metric selection process, it closes with ten commandments for more meaningful brand measurement.